New iron(II) cyclopentadienyl derivative complexes: synthesis and antitumor activity against human leucemia cancer cells - Valente, Andreia (2015)
A new family of "Fe-II(eta(5)-C5H5)" half sandwich compounds bearing a N-heteroaromatic ligand coordinated to the iron center by a nitrile functional group has been synthesized and fully characterized by NMR and UV-Vis spectroscopy. X-ray analysis of single crystal was achieved for complexes 1 and 3, which crystallized in the monoclinic P2(1)/c and monoclinic P2(1)/n space groups, respectively. Studies of interaction of these five new complexes with plasmid pBR322 DNA by atomic force microscopy showed very strong and different types of interaction. Antiproliferative tests were examined on human leukemia cancer cells (HL-60) using the MTT assay, and the IC50 values revealed excellent antiproliferative activity compared to cisplatin. (C) 2014 Elsevier B.V. All rights reserved.